PROFIL KEPERCAYAAN DIRI PESERTA DIDIK SMP (Studi Deskriptif Terhadap Peserta Didik Kelas IX SMP Negeri 1 SelaawiTahun Pelajaran 2019/2020) - Rohana Rohana; Wikanengsih Wikanengsih; Rima Irmayanti (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2020)
The purpose of this study was to describe the self-confidence profile of class IX students of SMP Negeri 1 Selaawi Garut. Self-confidence is the belief to do something to the subject as a personal characteristic in which there is confidence in self-ability, optimism, objectivity, responsibility, rational and realistic. This research was conducted at SMP Negeri 1 Selaawi Garut on 32 grade students consisting of 11 boys and 21 girls. . This research approach is a quantative approach and descriptive method with data collection tools, namely the interview guide student confidence. Based on the results of the study, it is known that the self-confidence of students of class IX SMP Negeri 1 Selaawi Garut is 29% of students in the low category. The factors that affect students' self-confidence are academic success, physical appearance, economic status, and environmental interaction.Keywords: : self-confidence, students